On the Status of Osprey in Georgia - Aleksandre Abuladze (Пернатые хищники и их охрана)
At present Osprey (Pandion haliaetus) is widespread and regular, but rare in small numbers passage visitor. Before the 1940’s it was a local breeder in small numbers at wetlands of the Black Sea coastlands, western part of Kolkheti Lowland and on wetlands in floodplains of some large rivers, and at large lakes in other regions of Georgia. Osprey extirpated as a regular breeder in the middle of 20th Century, no nests known since the late 1950’s. Last occupied nest was found in 1958 on Inkit Lake in Abkhazia. Analyzes of the historical data allows to suggest that before 1920’s osprey was widespread and regularly breeding species for some regions of Georgia.